Practical approach to linear endoscopic ultrasound examination of the rectum and anal canal - Okasha, Hussein Hassan; Pawlak, Katarzyna M.; Abou-elmagd, Amr; El-Meligui, Ahmed; Atalla, Hassan; Othman, Mohamed O.; Elenin, Sameh Abou; Alzamzamy, Ahmed; Mahdy, Reem Ezzat (Endoscopy International Open, 2022)
Standard endosonographic examination of the rectal area is usually performed with radial endoscopic ultrasound (EUS). However, in recent years, widespread availability of linear EUS for assessing various anatomical regions in the gastrointestinal tract has facilitated its use in the assessment of anorectal disorders. Currently, many rectal and anal diseases, including perianal abscesses, fistulae, polyps, and neoplastic lesions, can be well-visualized and evaluated with linear EUS. The aim of this review is to shed light on the anatomy and systematic examination of the anorectal region with linear EUS and clinical implications for different anorectal pathologies.